2017
DOI: 10.1055/s-0043-119223
|View full text |Cite
|
Sign up to set email alerts
|

Stress Fracture Influences Bone Resorption marker (u-NTX) in Female Long Distance Runners

Abstract: In this study, we aim to clarify the influence based on bone resorption markers at onset of stress fracture. Also, we will clarify the state of the bone resorption markers of female long distance runners who have a history of stress fracture and also ones who routinely practices running long distances. Participants comprised 19 female long distance athletes. The survey period was 2011–2014, and we measured u-NTX as a bone resorption marker at least twice a year, taking the mean±SD of the periodic measured valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
6
1
1
Order By: Relevance
“…The higher values observed in our participants, compared with those of the above studies, was considered to have been affected by repetitive weight bearing from sprinting. These markers evidently increased in individuals with bone injuries, including stress fractures [27]; however, none of the participants in the present study experienced a bone injury at the time of the measurements. In our participants, the bone turnover markers decreased even with continued training and approached the adult premenopausal reference range over the 1-year study period.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The higher values observed in our participants, compared with those of the above studies, was considered to have been affected by repetitive weight bearing from sprinting. These markers evidently increased in individuals with bone injuries, including stress fractures [27]; however, none of the participants in the present study experienced a bone injury at the time of the measurements. In our participants, the bone turnover markers decreased even with continued training and approached the adult premenopausal reference range over the 1-year study period.…”
Section: Discussioncontrasting
confidence: 53%
“…The higher values observed in our participants, compared with those of the above studies, was considered to have been affected by repetitive weight bearing from sprinting. These markers evidently increased in individuals with bone injuries, including stress fractures [27]; however, This document was downloaded for personal use only. Unauthorized distribution is strictly prohibited.…”
Section: Discussionmentioning
confidence: 94%
“…In a sample of adolescent female cross-country runners, elevated bone markers were associated with a lower body mass index, menstrual irregularities, and lower estradiol and vitamin D levels. 2 In contrast, Fujita et al 14 measured bone resorption (urine N-Tx) twice per year in a small sample of female runners aged 19 to 34 years and found that while N-Tx values were normal during training, they increased when an SF occurred. These findings suggest that N-Tx may be a noninvasive way to identify SFs and monitor healing.…”
Section: Discussionmentioning
confidence: 97%
“…Depending on the duration of their LEA, athletes may also present with altered bone geometry compared to their healthy peers, particularly decreased trabecular area in weight-bearing bones such as the pelvis 38,139,140 . The lower bone density and weakened structure can lead to increased risk of bony stress injuries that in turn can lead to stress fractures, which results from imbalanced bone resorption and bone formation 79,114,145 . Such scenarios are especially problematic for female athletes because they tend to be at higher risk of developing bony stress injuries compared to their male counterparts due to anatomical and hormonal differences [146][147][148][149] .…”
Section: Bone Healthmentioning
confidence: 99%
“…estrogen, testosterone) on bone metabolism. In some cases of LEA, particularly those involving intentional restricted caloric intake, athletes may not get sufficient calcium and vitamin D, both of which are essential to generating new bone 85,141,142 As a result, 12–45% of athletes with LEA tend to have lower bone mineral density, between one and two standard deviations below the population average 38,114,139,143,144 . Depending on the duration of their LEA, athletes may also present with altered bone geometry compared to their healthy peers, particularly decreased trabecular area in weight-bearing bones such as the pelvis 38,139,140 .…”
Section: Performance and Health Impairments Of Lea And Red-smentioning
confidence: 99%